Misdiagnosed psychiatric manifestations in a rare disease: a case report of secondary anxiety syndrome in Cushing’s disease - Geng, Wenqi; Cui, Lijia; Li, Tao; Liu, Xueqing; Yao, Yong; Hong, Xia; Zhu, Huijuan; Lu, Lin; Wei, Jing (Frontiers in Psychiatry, 2023)
Diagnosing and treating secondary psychiatric symptoms with accuracy can be challenging in clinical settings. In this case study, we report on a female patient with Cushing's disease who was misdiagnosed with anxiety disorder during her first psychiatric visit. Following initial ineffective psychiatric intervention, unexplained hypokalemia, and hypothyroidism, the patient visited the endocrinology clinic and was diagnosed with Cushing's disease. During the medical and surgical procedures that followed, high doses of psychotropic medication were continued to treat persisting anxiety. After discharge, the patient developed autonomic dysfunction and impaired consciousness. Upon readmission, serotonin syndrome due to inappropriate psychiatric medication was diagnosed. The management of secondary psychiatric syndromes must be adapted to changes in the patient's primary condition, which necessitates interdisciplinary collaboration in general hospital settings.